A Profusion of Special Paths: Unraveling the Concept of Sonderweg (Global Journal of Human-Social Science, 2017)
The concept of a German Sonderweg is one that needs a certain degree of unraveling before assessing its validity because it has been used in various contexts to explain a variety of theses it is thus better to distinguish its different meanings before considering its defensibility Originally used in the early days of the Prussian Empire the concept arose from the pride felt by Prussians who looked back at their country s rapid rise to an imperial power from a tiny scattered agglomeration of Hohenzollern holdings lost in the greater territory of the Holy Roman Empire The Sonderweg was in their understanding a special course different from that of other European states since in only a generation from a non-entity Prussia ascended to being among the most prominent nation-states in Europe The word itself implies a Prussian exceptionalism for Sonderweg is a coupling of the German Sonder special particular and Weg path Another definition for the concept of Sonderweg is tied to Prussia s brisk industrialization which by the late nineteenth century secured Prussia into a manufacturing power and a war machine quite unrivalled in Europe The last and most controversial meaning of the Sonderweg is a teleological view of Germany s convergence to Nazism this latest variant of the term was employed by German historiographers after 1945 in an effort to make sense of the horrors of the war and seek in their history the elements that lead to Nazism